2017
DOI: 10.3389/fimmu.2017.01013
|View full text |Cite
|
Sign up to set email alerts
|

Decidual Macrophage Functional Polarization during Abnormal Pregnancy due to Toxoplasma gondii: Role for LILRB4

Abstract: During gestation, Toxoplasma gondii infection produces a series of complications including stillbirths, abortions, and congenital malformations. The inhibitory receptor, LILRB4, which is mainly expressed by professional antigen-presenting cells (especially macrophages and dendritic cells) may play an important immune-regulatory role at the maternal–fetal interface. To assess the role of LILRB4 during T. gondii infection, LILRB4−/− and T. gondii infected pregnant mouse models were established. Further, human pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 42 publications
3
47
0
Order By: Relevance
“…Both stimulation conditions have basal expression of these markers that fluctuate during polarization 72 . Thus, the ratio of CD86 to CD206 expression was used to assess protein changes associated with macrophage polarization 73 . The CD86:CD206 ratio increased significantly in M(IFN-γ) compared with M(IL4/IL13) conditions by 72 hours, while heterogenous expression was observed at earlier time points ( Fig 3D).…”
Section: Metabolic Imaging Validation: Macrophage Stimulation In 2d Imentioning
confidence: 99%
“…Both stimulation conditions have basal expression of these markers that fluctuate during polarization 72 . Thus, the ratio of CD86 to CD206 expression was used to assess protein changes associated with macrophage polarization 73 . The CD86:CD206 ratio increased significantly in M(IFN-γ) compared with M(IL4/IL13) conditions by 72 hours, while heterogenous expression was observed at earlier time points ( Fig 3D).…”
Section: Metabolic Imaging Validation: Macrophage Stimulation In 2d Imentioning
confidence: 99%
“…In a mouse model of myocardial infarction, inducing M2 macrophage polarization reduced left ventricular adverse remodeling and improved cardiac function [19]. During pregnancy-related disorders such as miscarriages [35] and spontaneous preterm labor [36], the polarization pattern of decidua macrophages skewed toward M1. Such M1 polarization could result in an excessive pro-inflammatory response at the maternal-fetal interface, and interrupt the normal maintenance of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…At the maternal‐foetal interface, the immune tolerance environment is maintained by cells with a type II T helper (Th2) phenotype . In normal pregnancy, M2 macrophages are the major decidual macrophage population; these macrophages secrete IL‐10, which promotes immune tolerance . M2 macrophages acquire a Th2 phenotype and express anti‐inflammatory cytokines or chemokines, such as IL‐10 and IL‐4, at the maternal‐foetal interface.…”
Section: Cellular Immunopathogenesis Of Toxoplasma Gondii Infection Dmentioning
confidence: 99%
“…Expression of Th1 cytokines is upregulated, leading to an imbalance of the Th1/Th2 ratio. It has been reported that T. gondii infection downregulates the expression of leucocyte immunoglobulin‐like receptor B4 (LILRB4) on decidual macrophages, which enhances M1 activation and reduces M2 tolerance by changing the expression of M1 and M2 membrane molecules . M1 macrophages secrete TNF‐α and synthesize iNOS, which promotes a pro‐inflammatory response .…”
Section: Cellular Immunopathogenesis Of Toxoplasma Gondii Infection Dmentioning
confidence: 99%
See 1 more Smart Citation